PENGARUH STRUKTUR MODAL, GOOD CORPORATE GOVERNANCE, DAN INFLASI TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2014-2018) - Yolanda Irma; Efni Yulia; Fitri Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of capital structure, good corporate governance, and inflation to financial performance at food and beverage company listed on the Indonesian Stock Exchange period 2014-2018. The population in this study includes all food and beverage company totaling 19 companies, while the research sample obtained through certain criteria amounting to 19 companies whitin the study 5 years period. The result showed that : there is a negative and significant effect of capital structure on the financial performance, there is a positive and significant effect of good corporate governance on the financial performance, and there is nothing effect Inflation on the financial performance.Keywords : Capital Structure, Good Corporate Governance, Inflation, Financial Performance